Voicing Religious Tolerance Through Qur'anic Interpretation: An Analysis of Kim Knott’s Thought - Kusnadi; Eko Zulfikar (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2024)
This article aims to explore the concept of religious tolerance through the interpretation of the Qur'an by analyzing Kim Knott's thoughts about insider/outsider. This is motivated by a social fact that is being polemic and viral regarding the request of one Christian to the Indonesian Ministry of Religion to reform the interpretation of the Qur'an. By using qualitative methods and content analysis techniques as well as Kim Knott's insider/outsider perspective approach, this article concludes that the insider/outsider perspective on the open letter of Christians sent to the Indonesian Ministry of Religious Affairs to reform the interpretation of the Qur’an, is seen as dividing religious communities in Indonesia. Although it received support from the majority of Christians (outsiders) and claimed that its request to the Ministry of Religious Affairs specifically to revise the interpretation of QS. al-A’raf [7]: 157 is an act of tolerance, in fact what he did was an act of intolerance that could damage harmony between Muslims and Christians. In the insider's perspective, the request is seen as too interfering with Islamic teachings and ignoring one of the indicators of religious moderation promoted by the Indonesian Ministry of Religious Affairs, namely tolerance. Some posts uploaded related to the request to reform the interpretation of the Qur’an on social media have indirectly become an embryo of intolerance of interfaith harmony, especially between Muslims and Christians.